Current issues of demography and training of demographers in Tuva - Ryazantsev, Sergey V.; Rostovskaya, Tamara K.; Davletshina, Leysan A. (The New Research of Tuva, 2022)
The article presents a comprehensive approach to substantiating the need for demographers in the Republic of Tuva. The authors summarize studies of the demographic development and situation in Tuva. We consider some issues of demographic education in Russia and teaching of certain disciplines in the Republic of Tuva. A special attention is paid to the normative and legal acts regulating the state demographic policy in the region. The data of Rosstat, including the Office of the Federal State Statistics Service for Krasnoyarsk Krai, the Republic of Khakassia and the Republic of Tuva, are taken into account. We have identified the key indicators characterizing the demographic situation in Tuva in the period from 1990 to 2021, including negative ones. There is an absence of measures aimed at reducing (neutralizing) the influence of such indicators. The need for experts capable of adequately assessing the current demographic situation who are ready to construct predictive models and design an adequate demographic policy is justified. It has been found out that organizations in the Republic of Tuva feel the need for professionals to fill vacant positions in 2022. We have analyzed some Tuvan educational organizations. The flagship university was identified — Tuvan State University (TuvSU). In the Republic of Tuva, 98.98 percent of all students study in this HEI. Educational programs that are being implemented at TuvSU have been studied, the possibility of both the introduction of particular demographic disciplines and the implementation of training of demographers in the region has been evaluated.